MENDAFTARKAN GUGATAN PERDATA MEALALUI SISTEM E-COURT DI TENGAH WABAH COVID-19 YANG MENGHARUSKAN SOCIAL DISTANCING - Pasaribu, Gabriel Fermianthes; Apriani, Rani (Peneliti.net, 2024)
Coronavirus disease 2019, abbreviated as COVID-19, is an infectious disease caused by SARS-CoV-2, a type of coronavirus. This disease caused the 2019-20201 coronavirus pandemic. In the midst of this pandemic, all community activities have stopped, the government has called for Social Distancing (social distance) by adjusting the distance between crowds of people. In the Supreme Court Circular No. 4 of 2020 concerning Guidelines for the Implementation of Tasks During the Period to Prevent the Spread of COVID-19. Declare to temporarily stop judicial activities within the Supreme Court and the Judicial Bodies under it Until May 29, 2020. Which means the trial process has temporarily stopped, in this paper I will discuss about registering lawsuits through the E-court system and the position of the E-court system in procedural law Civil law, and guidelines use the E-court system which is of course to educate the general public and maybe also lawyers who often register conventional lawsuits.